Morphological Characteristics of Pepper (Piper nigrum L.)Varieties ofNatar 1 and Natar 2 Tolerant of Shade Stress - fajar setia ningrum; chairani hanum; edison purba (Universitas Sumatera Utara, 2018)
FAJAR SETIA NINGRUM: Morphological characteristics of pepper varieties of Natar 1 and Natar 2 tolerant of shade stress, guided by CHAIRANI HANUM and EDISON PURBA.Morphological observations were a preliminary identification for screening of tolerant shade plants, the ability to form chlorophyll and the initial step of the plant to be able to avoid shade stress.The research was conducted at Cengkeh Turi, North Binjai Subdistrict (32 meters above sea) from April to June 2017. Research used Split Plot Design with main plot was shade (0%, 25%, 50% and 75%) and sub plot was pepper shrub (Natar 1 and Natar 2).The results showed that the shade stress treatment had significant effect on the observed variables of plant height, the number of leaves and the calculation of chlorophyll a, the best shade level was N1 (25%) with the highest yield.Both varieties of shrimp pepper used have different responses on the number of branches, stem diameter, total leaf area, chlorophyll b, total chlorophyll, fresh crown weight, fresh root weight, canopy dry weight and root dry weight, tolerant varieties ie varieties natar 1. The number of leaves and the diameter of the stem is increased in the combination of the large-size treatment depending on the variety. Keywords: characteristics, shade, varieties of pepper.